Study on the orthostatic changes in blood pressure among hypertensive patients aged 40 and above - Pham, Thi Bao Khanh; Pham, Thi Ngoc Anh; Nghiem, Thi Ngoc Anh; Nguyen, Khoa Hung; Tran, Huu Thanh; Le, Phuoc Hoang (Tạp chí Y Dược Huế, 2025)
Background: Numerous international studies have demonstrated that orthostatic hypotension and orthostatic hypertension are risk factors for cardiovascular events and mortality. In Vietnam, awareness and research on this issue remain limited. Objectives: 1) To assess changes in blood pressure from supine to standing. 2) To investigate the relationship between orthostatic blood pressure changes and risk factors and cardiac impairment. Methods: A cross-sectional study with a comparison group. The study group consisted of 70 hypertensive patients from the Department of Cardiology from June 2023 to December 2023. The control group consisted of 70 patients without hypertension who attended the Internal Medicine Clinic. Results: The prevalence of orthostatic hypertension in the hypertensive group (12.9%) was significantly higher than in the non-hypertensive group (2.9%) (p = 0.028 < 0.05). The prevalence of orthostatic hypotension in the hypertensive group (15.7%) was slightly lower than in the non-hypertensive group (18,6%). Among the hypertensive group, there was a significant association between a history of diabetes mellitus and orthostatic blood pressure changes (p = 0.034 < 0.05; OR = 3,17; 95% CI: 1,06 – 9,43); between left ventricular hypertrophy on ECG and orthostatic blood pressure changes (p = 0,038 < 0,05). In the hypertensive group, the prevalence of left ventricular hypertrophy was higher in those with orthostatic blood pressure changes (25,0%) compared to those without changes (6,0%). There was a positive correlation between standing systolic blood pressure and heart rate (r = 0,388; p = 0,001 < 0,05); between supine and standing systolic blood pressure with EF (r = 0,352; p = 0,003 < 0,05), (r = 0,319; p = 0,007 < 0,05); between supine, standing systolic blood pressure and supine diastolic blood pressure with PWV (r = 0,289; p = 0,015 < 0,05), (r = 0,344; p = 0,004 < 0,05), (r = 0,313; p = 0,008 < 0,05). Conclusion: The prevalence of orthostatic blood pressure changes in hypertensive patients is relatively high. Hypertensive patients need to be assessed for arterial stiffness indices, including PWV and ABI, to enable early detection and prediction of systolic blood pressure difference, thereby improving clinical monitoring. However, treatment-related factors, such as medication type, were not assessed and should be considered in future studies.